Think Leader, Think Different: Early-Career Women on Leadership in Life Sciences - Harrington,Tadhg; Daniell,Emma Pernilla (2025)
The life science industry has strong female representation at entry levels, yet women remain underrepresented in senior leadership roles. A range of structural and cultural barriers contribute towards this imbalance, one of which is the enduring association between leadership and masculine-coded traits. Masculine-coded traits, often termed as agentic (e.g., assertiveness and dominance), are often contrasted with communal traits, which are typically coded as feminine (e.g., empathy and support). Research continues to show a link between perceived leadership effectiveness and agentic traits. Although recent literature suggests a gradual shift towards more androgynous leadership ideals, little research has explored how early-career women in the life sciences perceive and potentially internalise these gendered expectations. This study addresses that gap by investigating whether emerging professionals themselves reinforce or challenge these leadership norms. The aim of this study was to explore how early-career women in the life sciences perceive effective leadership and whether these perceptions reflect traditionally masculine, feminine, or androgynous ideals. Specifically, the research sought to understand which traits these women associate with effective and ineffective leadership, and to what extent those preferences are implicitly gendered. To fulfil these aims, ten semi-structured interviews were conducted with early-career female professionals in the life sciences sector. Thematic analysis of the data generated four overarching themes and thirteen subthemes. The results from the study indicated that early-career women in life sciences do not appear to conform to the association between effective leadership and masculine traits. Instead, participants expressed a clear preference for communal, relational, and support-oriented traits, while expressing negative opinions on overly masculine-coded or neutral traits. When agentic traits were valued, they were typically balanced by or embedded within communal behaviours. This suggests that participants are not simply rejecting masculine-coded leadership but are instead aspiring towards a more androgynous model, which blends agency with communality. Many participants also expressed aspirations to lead in transformative and inclusive ways, highlighting a desire to define leadership on their own terms.
Keywords: Agentic; communal; androgynous; leadership; 'think-leader; think-male'; life sciences; gender and leadership; and early-career women.